VD_FINDINFO Décision / 2014 / 725 vom 4. Juli 2014 - VD Tribunal cantonal (2014)
ACTE D'ORDRE SEXUEL AVEC UN ENFANT, CONTRAINTE SEXUELLE, CLASSEMENT DE LA PROCÉDURE | 187 CP, 189 CP, 319 CPP (CH), 39 PPMin